2019
DOI: 10.35808/ijeba/316
|View full text |Cite
|
Sign up to set email alerts
|

Social Constructs in Predicting Corruptive Attitudes and Behavior From Theory of Planned Behavior Perspective

Abstract: Purpose: This research examines the attitude and behavior corruption/fraud using the social construct, the theory of fraud triangle, the theory of planned behavior and social psychology. Design/methodology/approach: The quantitative approach in this study was carried out by collecting survey data using a questionnaire directly to 400 respondents in some cities in Indonesia. The analysis is conducted with SPSS, Wrap-PLS, Structural Equation Model (SEM) to test the hypotheses. Findings: The results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Overall, the suggested approach that we used in the research -the theory of planned behaviordemonstrated that it can explain 52% of relations in the model. This approached has already proved its efficiency by hundreds of researchers in the wide range of subject fields, starting with psychology (Romano & Netland, 2008) and environmental sciences (Turaga et al, 2010) and ending with business studies (Zulaikha et al, 2019) and even political science (Bosnjak et al, 2020). Our research has also confirmed its efficiency for the studies that aim at explaining human behavior.…”
Section: Findings and Discussionsupporting
confidence: 55%
“…Overall, the suggested approach that we used in the research -the theory of planned behaviordemonstrated that it can explain 52% of relations in the model. This approached has already proved its efficiency by hundreds of researchers in the wide range of subject fields, starting with psychology (Romano & Netland, 2008) and environmental sciences (Turaga et al, 2010) and ending with business studies (Zulaikha et al, 2019) and even political science (Bosnjak et al, 2020). Our research has also confirmed its efficiency for the studies that aim at explaining human behavior.…”
Section: Findings and Discussionsupporting
confidence: 55%
“…Studies conducted on working adults in Malaysia show that stress affects the employee's intention to commit fraud (Mat et al, 2019). This is supported by findings from Zulaikha et al (2019) that financial stress is directly proportional to corrupt behavior. Thus, it can be hypothesized that: H5: There is a positive effect of financial pressure on intention to commit unethical behavior.…”
Section: Financial Pressurementioning
confidence: 78%
“…The main objective of reforms, as a rule, is to eliminate the negative manifestations of the exercise of power, including malfeasance. Presently, researchers note the continued relevance of the problems of ensuring anti-corruption control over the activities of officials (Zulaikha et al, 2019). The problem of political self-isolation of the bureaucracy, which negatively affects the level of competence, has not yet been overcome (Mueller, 2015).…”
Section: Relevance Of the Research Taskmentioning
confidence: 99%